Treadmill Training Improves Forward and Backward Gait in Early Parkinson Disease. (October 2015) - Tseng, Ing-Jy; Yuan, Rey-Yue; Jeng, Chii
ABSTRACT: Objective: The aim of this study was to examine effects of treadmill training (TT) and lasting duration of training effects on forward walking (FW) and backward walking (BW) gait in Parkinson disease (PD). Design: Twenty-six early PD patients undertook a 12-wk intensive TT program using FW. A repeated-measures design compared GAITRite-measured FW and BW gait before TT, within 1 wk, and at 4 and 12 wks after TT. Results: Twenty-three PD patients, after completing TT, walked forward and backward with increased velocity, enlarged stride length, prolonged swing phase, and decreased double support phase; improvements occurred within 1 wk and remained at 4 and 12 wks after training ( P < 0.01 or < 0.001). In addition, trends toward reduced posttraining swing time variability and stride length variability occurred in both directions and sustained for 12 wks. Posttraining FW and BW gait improvements were comparable. BW deficits, regardless of training, constantly exceeded FW deficits. Cadence did not differ before and after training in FW ( P = 0.195) and BW ( P = 0.229) and between FW and BW irrespective of TT ( P = 0.124). Conclusions: A 12-wk TT program improves the 12-wk duration of FW and BW gait and can be considered a part of a rehabilitation strategy to overcome gait disturbances in early PD.